Application of crispr/cas9-based reverse genetics in leishmania braziliensis: Conserved roles for hsp100 and hsp23 - Adaui, Vanessa (2020)
The protozoan parasite Leishmania (Viannia) braziliensis (L. braziliensis) is the main cause of human tegumentary leishmaniasis in the New World, a disease affecting the skin and/or mucosal tissues. Despite its importance, the study of the unique biology of L. braziliensis through reverse genetics analyses has so far lagged behind in comparison with Old World Leishmania spp. In this study, we successfully applied a cloning-free, PCR-based CRISPR–Cas9 technology in L. braziliensis that was previously developed for Old World Leishmania major and New World L. mexicana species. As proof of principle, we demonstrate the targeted replacement of a transgene (eGFP) and two L. braziliensis single-copy genes (HSP23 and HSP100). We obtained homozygous Cas9-free HSP23-and HSP100-null mutants in L. braziliensis that matched the phenotypes reported previously for the respective L. donovani null mutants. The function of HSP23 is indeed conserved throughout the Trypanosomatida as L. major HSP23 null mutants could be complemented phenotypically with transgenes from a range of trypanosomatids. In summary, the feasibility of genetic manipulation of L. braziliensis by CRISPR–Cas9-mediated gene editing sets the stage for testing the role of specific genes in that parasite’s biology, including functional studies of virulence factors in relevant animal models to reveal novel therapeutic targets to combat American tegumentary leishmaniasis.